Theoretical Modeling of the Surface-Enhanced Raman Optical Activity - Novák, Vít; Šebestík, Jaroslav; Bouř, Petr (Journal of chemical theory and computation, 2012)
Surface-enhanced Raman optical activity (SEROA) is a new technique combining the sensitivity of the surface-enhanced Raman scattering (SERS) with the detailed information about molecular structure provided by the chiral spectroscopies. So far, experimental SEROA spectra have been reported in several studies, but the interpretation and theoretical background are rather limited. In this work, general expressions for the electromagnetic contribution to SEROA are derived using the matrix polarization theory and used to investigate the enhancement in model systems. The results not only reveal a strong dependence of the enhancement on the distance between the molecule and a metal part but also the dependence of the ratio of ROA and Raman intensities (circular intensity difference, CID) on the distance and rotational averaging. For a ribose model, an optimal molecule-colloid distance was predicted which provided the highest CIDs. However, the CID maximum disappeared after a rotational averaging. For cysteine zwitterion, the simulated SEROA and SERS spectra provided a qualitative agreement with previous experiments.